Sertifikasi Guru menuju Profesionalisme Pendidik - Muhammad Nasrul Waton (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2016)
An educator or teacher greatly affect the quality of education, because the role of a teacher is to teach a wide range of knowledge to their students. Competence of teachers teaching agent formally evidenced by a certificate of educators. The minimum academic qualifications acquired through higher education, and educators competency certificates obtained after passing the certification exam. The position of teachers as professionals aim to implement the national education system and achieve national education goals, namely the development of students' potentials to become a man of faith and devoted to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and became citizens of a democratic and responsible